Prevalence of Vitamin D Deficiency Among Antenatal Cases Between Vitamin D Levels and the Possibility of Adverse Pregnancy Outcome - Sanobar Baloch, Sumaiya Farooq, Shazia Awan, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: From the beginning till delivery, the embryo relies solely on its mother for all of its nutritional needs. There is a direct link between 25-OHD insufficiency and bad pregnancy outcomes, including preterm and congenital abnormalities. The study's goals were to find out how common deficiencies are among pregnant women at Indus Medical Hospital and to see if there's a link between those deficiencies and pregnancy difficulties. Material and Methods: Over six months, researchers examined the 25(OH)D levels and obstetrical problems, and risk-factors of 90 women. I observed 25-OHD deficiency in 43 pregnant women, according to the results. Results: A total of 90 pregnant women were enrolled, of these, 43 (47.77%) women had vitamin D deficiency. 34 (37.77%) of the females did not ate non-vegetarian foods and 20 (22.22%) ate non-vegetarian meals every other day. Milk intake was likewise low, with 37 (41.11%) drinking it every other day or fewer; the normal serving size of milk was 150 ml. Women below 30 years of age of 23 (53.48%), housewives of 22 (51.16%), and low-income households of 20 (46.51%) showed significantly lower vitamin D levels than women with higher socioeconomic status. Women with low 25(OH)D levels and pregnancies that resulted in over 34 (79.06%) low birth weight babies (<2.5kg) were more likely to experience growth restriction. The baby's growth in utero appears to be being affected by maternal deficiencies. Conclusions: In conclusion, we observed that the frequency of 25(OH)D insufficiency was quite high.